Supporting the Transition to Higher Education: Finnish Principals' Views on Opportunities and Challenges of Institutional Cooperation - Topias Ikävalko; Johannes Pernaa; Maija Aksela (MDPI AG, 2023)
The transition from upper secondary school to higher education is a major change in students' lives. Supporting students to make informed decisions based on a realistic view of higher education is one of the key elements to ensuring their motivation in future studies. Cooperation between upper secondary and higher education is one model for providing students with realistic views. However, little research has been produced from this cooperation. Therefore, the aim of this paper, based on mixed-method research, is to produce new insights into the opportunities provided by institutional cooperation by analyzing the views of Finnish upper secondary school principals (N = 94). The data were gathered using an online survey and analyzed via qualitative content analysis and descriptive statistics. The results indicate that principals consider cooperation with higher education institutions to be beneficial but there are some challenges in its implementation, such as the different structures of upper secondary schools and universities and inadequate information about possible opportunities. There are also great differences in upper secondary schools' levels of participation. Distance to the nearest higher education institution and the size of the upper secondary school affected the participation models. There is a need to support cooperation between institutions to ensure equal possibilities for students, such as common structures, better information, as well as a multitude of different opportunities.